Acute small bowel obstruction due to retrocecal hernia: A surgical case report - Fatnassi, Oumayma; Maatouk, Mohamed; Mabrouk, Aymen; Bahloul, Mohamed Ali; Ben Moussa, Mounir (Indian Journal of Case Reports, 2025)
Small bowel obstruction due to internal hernias is a well-known clinical challenge for surgeons. Among these, pericaecal hernias are particularly rare. Prompt diagnosis and timely surgical intervention are crucial to prevent complications such as strangulation and bowel necrosis. We present the case of a 64-year-old man with no prior abdominal surgery who presented to our emergency department with a history of abdominal pain and vomiting. Clinical evaluation and abdominal computed tomography scan revealed a small bowel obstruction. Following appropriate resuscitation, the patient underwent emergency laparotomy, which revealed a herniated loop of ileum through a retrocecal defect as the underlying cause of the obstruction. The herniated bowel was successfully reduced. Despite its rarity, pericaecal hernia must be kept in mind when evaluating patients with small bowel obstruction.